Genetic Variations within the Bovine CRY2 Gene Are Significantly Associated with Carcass Traits - Xuelan Li; Enhui Jiang; Kejing Zhang; Sihuan Zhang; Fugui Jiang; Enliang Song; Hong Chen; Peng Guo; Xianyong Lan (Animals, 2022)
As an important part of the circadian rhythm, the circadian regulation factor 2 of cryptochrome (CRY2), regulates many physiological functions. Previous studies have reported that CRY2 is involved in growth and development. However, the relationship between CRY2 gene polymorphism and cattle carcass traits remains unclear. The aim of this study was to detect the possible variations of the CRY2 gene and elucidate the association between the CRY2 gene and carcass traits in the Shandong Black Cattle Genetic Resource (SDBCGR) population (n = 705). We identified a 24-bp deletion variation (CRY2-P6) and a 6-bp insertion variation (CRY2-P7) in the bovine CRY2 gene. The frequency of the homozygous II genotype is higher than the heterozygous ID genotype in both two loci. In addition, CRY2-P6 was consistent with HWE (p > 0.05). Importantly, the CRY2-P6 variant was significantly associated with 12 carcass traits, including gross weight, ribeye, high rib, thick flank, etc. and the II was the dominant genotype. The CRY2-P7 site was also significantly correlated with five traits (gross weight, beef-tongue, etc.). Collectively, these outcomes indicated that the two Indel loci in the CRY2 gene could be used for marker-assisted selection of cattle carcass traits.